2008
DOI: 10.3346/jkms.2008.23.6.1121
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell "Sugar" Tumor of the Lung: A Well-Enhanced Mass with an Early Washout Pattern on Dynamic Contrast-Enhanced Computed Tomography

Abstract: Clear cell tumor of the lung is a rare and very unusual benign pulmonary tumor. As clear cell tumor of the lung contains abundant cytoplasmic glycogen, this tumor is called "sugar tumor". We report a case of sugar tumor in a 64-yr-old man presenting as a round pulmonary nodule. On dynamic computed tomography (CT) scans, the solitary pulmonary nodule showed early wash-in enhancement with an early washout pattern like a lung malignancy. The patient underwent wedge resection for the tumor. Pathologic examination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 18 publications
(28 reference statements)
3
35
1
2
Order By: Relevance
“…They also seem to mostly affect the elderly. 5 However, there has been a report of an 8-year-old with the tumor. 6 Unfortunately, not enough cases have been reported to establish specific risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also seem to mostly affect the elderly. 5 However, there has been a report of an 8-year-old with the tumor. 6 Unfortunately, not enough cases have been reported to establish specific risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…3 Usually, sugar tumors are discovered inadvertently via radiologic films as solitary, round, pulmonary nodules 4 with no lobar preference. 5 Sugar tumors of the lung almost exclusively reside in the parenchyma, yet actual cellular origin remains unknown. 2 The neoplasm is made up of uniform, round, clear cells with welldefined borders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the rich vascular stroma, most CCTLs show homogenous intense enhancement on CT scans. Kim et al (8), reported an early wash-in and washout pattern of CCTL on dynamic CT. CCTLs usually show no 18 F-2-deoxy-D-glucose (FDG) uptake, but a 2.8-cm benign CCTL that showed extensive FDG uptake has been reported (9).…”
Section: Discussionmentioning
confidence: 99%
“…The sugar tumor may occur in any lobe and is mainly located under the pleura, with no communication with the bronchi [3]. It occurs in all age groups, but is most often seen in the elderly, and affects both sexes equally [4].…”
Section: Introductionmentioning
confidence: 99%